1996
DOI: 10.1021/jf950581p
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Denaturation and Aggregation of Chicken Breast Muscle Myosin and Subfragments

Abstract: To elucidate the roles of the head and tail portions of chicken breast muscle myosin in gelation, the thermal stability and aggregation behavior of myosin and seven subfragments in 0.6 M NaCl, pH 6.5, were investigated, namely, myosin heavy chain (MHC), light chains (LC), heavy meromyosin (HMM), light meromyosin (LMM), rod, subfragment 2 (S-2), and subfragment 1 (S-1). Myosin had four independent cooperative endothermic transitions (T m) at 47, 54, 57, and 63 °C and aggregated from 50 to 70 °C. The MHC endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
40
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 32 publications
14
40
0
1
Order By: Relevance
“…For chicken myosin (0.6 M NaCl), the HMM-S2 transitions have been claimed to occur at higher temperatures (>55°C) than the LMM subunit. In the same study the transition temperatures of myosin light chains were reported to occur at 48 and 57°C (Smyth, Smith, Vega-Warner, & O'Neill, 1996).…”
Section: Pre-saltingmentioning
confidence: 78%
See 1 more Smart Citation
“…For chicken myosin (0.6 M NaCl), the HMM-S2 transitions have been claimed to occur at higher temperatures (>55°C) than the LMM subunit. In the same study the transition temperatures of myosin light chains were reported to occur at 48 and 57°C (Smyth, Smith, Vega-Warner, & O'Neill, 1996).…”
Section: Pre-saltingmentioning
confidence: 78%
“…The two stages of melting of proteins with an a-helical structure has been explained by a decrease in the inter-chain interaction and an unfolding of the helical structure. The helical structure is primarily destabilised by changes in electrostatic and hydrophobic interactions (Samejima, Ishioroshi, & Yasui, 1983;Smyth, Smith, Vega-Warner, & O'Neill, 1996).…”
Section: Evaluation Of the Dsc Of The Fresh Cod Musclementioning
confidence: 99%
“…Typical thermal transition temperatures for meat proteins range from 43 to 67°C for myosin and its subunits, 67 to 69°C for sarcoplasmic proteins, and 71 to 83°C for actin (Smyth, Smith, Vega-Warner, & O'Neill, 1996). SSMP is mainly composed of myosin, of which peak values of thermal transition temperature were 40.9-63.3°C (T peak1 ) for myosin head (heavy meromyosin) and 62.2-68.6°C (T peak2 ) for myosin tail (light meromyosin) (Amako & Xiong, 2001;Chen et al, 2007;Nagai et al, 1999).…”
Section: Dscmentioning
confidence: 99%
“…Wang and Smith (1994a) identified in the myosin isolated from the chicken breast muscle ten different protein domains. Smyth et al (1996) showed that the domain containing α-helix of light meromyosin was unfolded as a result of heating within the temperature range of 20-46°C. This suggests a thermal process of partial unfolding of myosin, as a result of which new, previously unavailable hydrophilic and hydrophobic groups were revealed.…”
Section: Resultsmentioning
confidence: 99%